Cu–Ni alloy decorating N-doped carbon nanosheets toward high-performance electrocatalysis of mildly acidic CO2 reduction. Issue 8 (20th March 2023) - Pan, Weifan; Wang, Peng; Fan, Linfeng; Chen, Kai; Yi, Luocai; Huang, Junheng; Cai, Pingwei; Liu, Xi; Chen, Qingsong; Wang, Genxiang; Wen, Zhenhai
Abstract : The nitrogen-doped "willow leaf" shaped carbon nanosheets modified with Cu-Ni alloy shows excellent electrocatalytic activity for reducing CO2 to CO under mildly acidic media. Abstract : Electrochemical CO2 reduction to value-added chemicals or fuels is a prospective strategy for facilitating the closing of the carbon loop. However, there still exist challenges in developing efficient catalysts and optimizing the electrolyzer components to meet industrial applications. Herein, nitrogen-doped "willow leaf" shaped carbon nanosheets modified with Cu–Ni alloy (CuNi-N-CNS) is designed for electrochemical CO2 reduction reaction (CO2 RR), which shows high faradaic efficiency for CO of over 90% at a wide potential window ranging from −0.8 V to −1.0 V and robust durability with almost 100% of its initial selectivity after 36 h of electrolysis in H-type cell. Moreover, we evaluate its electrocatalytic activity in a self-assembly flow cell in a mildly acidic catholyte (CO2 -saturated 3 M KCl solution, pH = 4.25), which can achieve a commercially viable current density of 420 mA cm −2 at −1.0 V versus reversible hydrogen electrode ( vs. RHE) with CO selectivity above 95%. Experimental characterization and electrochemical analysis reveal that the synergistic effects of ultra-thin "willow leaf" structure and bimetallic alloy modification can not only increase electron transport efficiency but also decrease the reaction energy barrier of COOH* and promote the formation of CO.